NEW HERMITE-HADAMARD TYPE INEQUALITIES VIA CONFORMABLE FRACTIONAL INTEGRALS CONCERNING DIFFERENTIABLE RELATIVE SEMI-(r; m; h1; h2)-CONVEX MAPPINGS AND THEIR APPLICATIONS - Kashuri, Artion; Iqbal, Sajid (Matematichki Bilten, 2020)
In this article, we first presented a new identity via conformable fractional integrals. By applied the concept of relative semi-\((r;m,h_1,h_2)\)-convexity and the obtained identity as an auxiliary result, some new estimates with respect to the left hand side of the Hermite–Hadamard type inequalities via conformable fractional integrals are given. Also, some applications to special means and error estimates for the midpoint formula are provided as well.